CLINICAL IMPLICATIONS OF LUCID DREAMING RESEARCH (FOR PSYCHOSIS, NIGHTMARES, PTSD) - Ritu Choudhary (International Journal of Multidisciplinary Research and Studies, 2021)
Both Kant and Schopenhauer drew attention to the fact that there is a connection between lucid dreaming and psychosis. Specifically, the two philosophers proposed that "a lunatic is a wakeful dreamer" and that "a dream is a short-lasting psychosis, and a psychosis is a long-lasting dream," respectively. Wundt said that "we may encounter in dreams all the phenomena we find in the reality," which agrees with both of these ideas. Sigmund Freud, who proposed that psychosis is an aberrant incursion of a dreaming activity into an awake state was inspired in various ways by all of these individuals. Emil Kraepelin, while being one of the most prominent critics of psychoanalysis, postulated the same thing.